2006
DOI: 10.1111/j.1365-313x.2006.02821.x
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast lumen and stromal proteomes of Arabidopsis thaliana show differential sensitivity to short‐ and long‐term exposure to low temperature

Abstract: ). † The first two authors contributed equally to this paper, and this work is the result of an equal collaboration between the laboratories of the last two authors. SummaryCold acclimation and over-wintering by herbaceous plants are energetically expensive and are dependent on functional plastid metabolism. To understand how the stroma and the lumen proteomes adapt to low temperatures, we have taken a proteomic approach (difference gel electrophoresis) to identify proteins that changed in abundance in Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 90 publications
8
161
0
3
Order By: Relevance
“…Washing and elution of proteins coimmunoprecipitated with PSB33 were performed according to the manufacturer's instructions (Pierce Crosslink Magnetic Co-IP Kit 88805). The eluted proteins were separated on a 15% (v/v) polyacrylamide gel and stained with silver as described (Goulas et al, 2006). In-gel digestion of selected protein bands was performed as described (Fristedt and Vener, 2011).…”
Section: Antibody Productionmentioning
confidence: 99%
“…Washing and elution of proteins coimmunoprecipitated with PSB33 were performed according to the manufacturer's instructions (Pierce Crosslink Magnetic Co-IP Kit 88805). The eluted proteins were separated on a 15% (v/v) polyacrylamide gel and stained with silver as described (Goulas et al, 2006). In-gel digestion of selected protein bands was performed as described (Fristedt and Vener, 2011).…”
Section: Antibody Productionmentioning
confidence: 99%
“…At1g23740 protein has a predicted transit peptide in the Nterminal region and has been identified as a stromal protein in chloroplasts by two independent proteomic analyses (23,24). Accordingly, we concluded that AtAOR was the chloroplastlocalizing AOR.…”
Section: Purification Of Acrolein-reducing Enzyme From Cucumbermentioning
confidence: 80%
“…The GST proteins have been shown to respond to various stresses such as HL, cold, and drought (Wagner et al, 2002;Seki et al, 2003;Goulas et al, 2006). After exposure to HL, six different GST genes were induced, and four of them were induced in both HL and high intensity BL (Supplemental Tables S1 and S2).…”
Section: Discussionmentioning
confidence: 99%